Joint Statement of EFSA and EMA on the presence of residues of phenylbutazone in horse meat. (15th April 2013) - ,
Abstract: Controls in Member States have revealed the presence of phenylbutazone in horse carcasses intended for the food chain. Following the request from the European Commission, the European Medicines Agency and the European Food Safety Authority jointly concluded on the risk assessment on residues of phenylbutazone in horse meat in the context of recent fraudulent practices. The Committee for Veterinary Medicinal Products assessed the consumer safety for phenylbutazone in 1997 and identified the main risks for the consumer as idiosyncratic blood dyscrasias and the genotoxic/carcinogenic potential for which no thresholds could be identified and no maximum residue limits could be established. The substance can therefore not be used in animals destined to enter the food chain. These main risks have been re‐confirmed in the present statement as no new relevant information has become available since the initial safety assessment. Exposure to phenylbutazone from horse meat consumed as such or present in beef‐based products was assessed on the basis of limited monitoring data provided by 19 Member States and of conservative assumptions. Up to 144 and up to 36 800 individuals per 100 million could be potentially exposed across countries and age groups each day. On a given day, the probability of a consumer being both susceptible to developing aplastic anaemia and being exposed to phenylbutazone was estimated to range approximately from 2 in a trillion to 1 in 100 million. The risk of carcinogenicity to humans from exposure was considered very low based on the available experimental data on organ toxicity and carcinogenicity, as well as on the low exposure levels and the infrequent exposure to phenylbutazone from horse meat or adulterated beef‐based products. Measures proposed to further minimise the risk include strengthening of the horse passport system, harmonised monitoring of phenylbutazone and its main metabolite and better reporting of monitoring of veterinary drug residues and other substances across the EU.